Filogenia molecular de Brucepattersonius (Sigmodontinae: Akodontini) com uma análise morfométrica craniana do gênero - Vilela, Júlio Fernando (2005)
In the attempt to identify evolutionary units in the genus Brucepattersonius and to propose a phylogeneti hypothesis for them, morphometric and molecular analyses were carried out on samples enpompassing a wide are a ofthe distribution ofthe genus. Both analyses sorted the available samples into tive independent units: Lineage “A”, from the Caparaó massif, state of Minas Gerais, was shown to belong to only one species, namely B. griserufescens, in as much as the holotype of B. a/binasus, described for the same locality, was not distinct from it in molecular terms (cyt. b sequence). Lineage “B”, from Órgãos and Mantiqueira mountains (Rio de Janeiro and Minas Gerais), could not be assigned to any ofthe available nominal fom1s in the genus. Lineage “C”, clustered samples from São Paulo states to an haplotype that occurred in simpatry with specimens of Lineage “B” from Mantiqueira mountains. Lineage “D”, composed by specimens from Aratiba, state of Rio Grande do Sul, was shown to be morphometrically related to one of the three species described from the province of Misiones, Argentina. Lineage “E”, represented by a sole specimen from Urubici, state of Santa Catarina, is a divergent undescribed formo These tive units, restricted to the Atlantic Forest morphoclimatic domain, have shown a strong geographic structure: a basal group, predominantly meridional in distribution, with an offshot dispersed into the Mantiqueira montains; an isolated form in the Serra Geral of Santa Catarina; and a more derived group, with two species, one from the Caparaó massif, and the another from Órgãos and Mantiqueira mountains.